2022
DOI: 10.3389/fmicb.2022.919207
|View full text |Cite
|
Sign up to set email alerts
|

Strategy to Evaluate Changes in Bacterial Community Profiles and Bacterial Pathogen Load Reduction After Sewage Disinfection

Abstract: Sewage effluent discharge is a major source of pathogenic contamination to the environment. The disinfection process is critical for the elimination of pathogens in sewage. In this study, we examined the impact of chlorine disinfection on the total, viable, and culturable populations of indicator bacteria, pathogens, and bacterial communities in two contrasting types of effluents (primarily treated saline and secondarily treated freshwater). Effluents collected bimonthly over 1 year were examined using cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…144 Tang et al found that PMA-qPCR was effective in detecting viable bacteria in chlorine-disinfected wastewater. 145…”
Section: Methods For Targeting the Dnasmentioning
confidence: 99%
“…144 Tang et al found that PMA-qPCR was effective in detecting viable bacteria in chlorine-disinfected wastewater. 145…”
Section: Methods For Targeting the Dnasmentioning
confidence: 99%
“…Differences of less than 3.2 (equivalent to 91.9% efficiency) were regarded as amplification inhibition, and a higher level of dilution would be needed to alleviate the inhibition. The final gene copy numbers were corrected by the DNA extraction and PMA treatment efficiencies using the recovered gene copies of the extraction and PMA controls (Tang & Lau, 2022), calculated as below: lefttrueExtraction efficiency%=Detected TaqMan controlDNAcopySpiked TaqMan controlDNAcopy×100%$$ \mathrm{Extraction}\ \mathrm{efficiency}\left(\%\right)=\frac{\mathrm{Detected}\ \mathrm{TaqMan}\ \mathrm{control}\ \mathrm{DNA}\ \mathrm{copy}}{\mathrm{Spiked}\ \mathrm{TaqMan}\ \mathrm{control}\ \mathrm{DNA}\ \mathrm{copy}}\times 100\% $$ normalPMA0.25emefficiency%=lefttrue1Detected salmonDNAcopySpiked salmonDNAcopy×100%$$ \mathrm{PMA}\ \mathrm{efficiency}\left(\%\right)={\displaystyle \begin{array}{l}\left(1-\frac{\mathrm{Detected}\ \mathrm{salmon}\ \mathrm{DNA}\ \mathrm{copy}}{\mathrm{Spiked}\ \mathrm{salmon}\ \mathrm{DNA}\ \mathrm{copy}}\right)\\ {}\times 100\%\end{array}} $$ …”
Section: Methodsmentioning
confidence: 99%
“…To quantify the viable populations of total bacteria, Enterococcus and E. coli , the samples were treated with PMA before DNA extraction, following the procedures in our previous study (Tang & Lau, 2022 ). Briefly, triplicates of 500‐mL aliquots from each sample were centrifuged and resuspended in autoclaved PBS, then added with a final concentration of 100 μM of PMA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations